Back Cover: The Synthesis of Conical Carbon (Small Methods 3/2021). Issue 3 (15th March 2021) - Zhang, Qianyan; Xie, Xiao‐Ming; Wei, Shi‐Yao; Zhu, Zheng‐Zhong; Zheng, Lan‐Sun; Xie, Su‐Yuan
Abstract : The cone angles of carbon nanocones (CNCs) or carboncones are determined by the number of pentagons (1–5) in the cone tip. CNCs are multi‐walled conical carbon structures produced by traditional physical‐chemical methods, while carboncones are single‐walled conical carbon structures prepared by the emerging bottom‐up organic approaches. The advantage of organic approaches is the fabrication of conical carbons with well‐defined single‐walled structures. The synthesis of conical carbon is reviewed by Su‐Yuan Xie and co‐workers in article number 2001086 .